1998
DOI: 10.1017/s1366728998000364
|View full text |Cite
|
Sign up to set email alerts
|

Producing words in a foreign language: Can speakers prevent interference from their first language?

Abstract: Two picture-word interference experiments were conducted to investigate whether or not words from a first and more dominant language are activated during lexical access in a foreign and less dominant language. Native speakers of Dutch were instructed to name pictures in their foreign language English. Our experiments show that the Dutch name of a picture is activated during initial stages of the process of lexical in English as a foreign language. We conclude that bilingual speakers cannot suppress activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
410
12
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(469 citation statements)
references
References 33 publications
(47 reference statements)
38
410
12
9
Order By: Relevance
“…In their seminal study, Hermans et al (1998) showed that when speakers have to name pictures in their L2 (in their case English), the L1 (in their case Dutch) translation of the target word is also activated up to the phonological level. In two picture-word interference experiments, participants were asked to name pictures of simple objects in their L2 (e.g.…”
Section: Cross-language Activation In Bilingual Word Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their seminal study, Hermans et al (1998) showed that when speakers have to name pictures in their L2 (in their case English), the L1 (in their case Dutch) translation of the target word is also activated up to the phonological level. In two picture-word interference experiments, participants were asked to name pictures of simple objects in their L2 (e.g.…”
Section: Cross-language Activation In Bilingual Word Productionmentioning
confidence: 99%
“…both languages are activated and spread information to the lexical nodes regardless of the target language (e.g. Costa, 2004;De Bot, 1992;Green, 1998;Hermans, Bongaerts, De Bot, & Schreuder, 1998). However, it is still debated whether lexical selection, too, is non-specific with respect to language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the other type of models assumes that the lexical selection mechanism is not specific to a given language (e.g., Green, 1986Green, , 1998Hermans et al, 1998;Poulisse and Bongaerts, 1994; also see Costa and Santesteban, 2004). According to these models, words in both languages are activated and the individual has to consider all activated lexical nodes, irrespective of the language to which they belong.…”
Section: Introductionmentioning
confidence: 99%
“…W. Green, 1998;Hermans, Bongaerts, De Bot, & Schreuder, 1998;Jared & Kroll, 2001;Rodriguez-Fornells et al, 2005;Van Hell & Dijkstra, 2002). More recent evidence for this joint interaction has isolated specific effects on phonological production in the target language (Costa, Roelstraete, & Hartsuiker, 2006) and shown the persistence of such influences even for two languages that are written in different types of writing systems (Hoshino & Kroll, 2008).…”
mentioning
confidence: 99%